The Impact of Digital Pattern Making-based Learning on Pattern Accuracy and Production Efficiency in Vocational Fashion Education - Nurhijrah; Wabdillah (Journal of Vocational, Informatics and Computer Education, 2025)
This study examined the effectiveness of digital pattern-making-based instruction in improving students’ pattern accuracy and production efficiency in vocational fashion education. The study specifically addressed the limited empirical evidence concerning the simultaneous evaluation of technical precision and workflow efficiency within vocational secondary school contexts in Indonesia. A quasi-experimental pretest–posttest control group design was employed involving 60 eleventh-grade students enrolled in the Fashion Design Program at SMK Negeri 8 Makassar, Indonesia. The participants were divided into an experimental group (n = 30) and a control group (n = 30). The experimental group received instruction using CAD-based digital pattern-making software (CLO 3D), while the control group received conventional manual pattern-making instruction. Data were collected using a performance assessment rubric and a structured time-recording instrument. The rubric evaluated measurement accuracy, pattern completeness, line consistency, and adherence to design specifications. Content validity was established through expert judgment involving vocational education specialists and fashion industry practitioners, while reliability testing produced a Cronbach’s Alpha coefficient of 0.89, indicating high internal consistency. The findings revealed that students who received digital instruction achieved significantly higher pattern accuracy (M = 84.72, SD = 5.21) than students in the control group (M = 71.36, SD = 6.03), t(58) = 9.18, p < 0.001, with a very large effect size (Cohen’s d = 5.63). The experimental group also demonstrated significantly higher production efficiency (M = 65.40 minutes) compared with the control group (M = 82.15 minutes), t(58) = -9.18, p < 0.001, with a large practical effect (Cohen’s d = 2.37). These findings indicate that digital pattern-making instruction effectively enhances technical competency and workflow efficiency in vocational fashion education.